Attività conoscitiva sull'Irap. Relazione finale - Commissione Bicamerale Riforma Fiscale (Moneta e Credito, 2012)
The article is the final report on TRAP of the Italian Parliamentary Commis-sion on Fiscal Reform (including both members of the Senate and of the Chamber of Deputies). TRAP,  a regional tax on productive activities newly introduced two years ago, is levied on value added (including interest pay-ments) produced by individual and corporate firms and professional activi-ties. It comes in substitution of a number of previous taxes (additional profit tax, health contributions on payroll and others). The Report analyses the impact of IRAP on firms' behaviour and the shifting of conveniences in adopting labour or capital saving productive pro-cesses, and its short-period impact on labour costs. It also analyses how tax burden is redistributed among firms. Finally, the Report reviews costs and benefits arising from possible revisions aimed at lowering the cost of labour and benefiting small firms.     JEL Code: H25.